Facturación y cumplimiento tributario - Serrano Aragón, María de los Ángeles (2024)
In 2013, the Ecuadorian Internal Revenue Service (SRI) officially implemented electronic invoicing as part of its institutional strategy to modernize the tax administration. This measure was intended to reduce tax evasion and simplify compliance by taxpayers. In 2015, the massive adoption of this new system by taxpayers took place. This study aims to determine the impact of electronic invoicing and the effects it has had on the tax compliance of companies in the Guaranda canton, which are obliged to use this new form of fiscal control. The present investigation has a mixed approach, of an exploratory and field type, since it is related to the search, collection, analysis and compilation of information. Subsequently, the questionnaire for data collection was applied, which was validated by experts in the study area, therefore, the instrument has sufficient validity and reliability in the questions asked. The results reveal significant effects on tax compliance, indicating that the Electronic Invoice in Ecuador has great potential to become the central tax control strategy of the Ecuadorian government. It can be concluded that the application of electronic invoicing in the businesses of the Guaranda canton, this has meant a great challenge for all businessmen, the lack of knowledge regarding the use of technology generates a great resistance to all the changes that the system of electronic invoicing represents, however, the Internal Revenue Service facilitates the application of this system for all its taxpayers.